The Brent Goose and its food supply in Essex - Burton, P J K (Wildfowl, 1961)
Surveys have been made of food supplies in the wintering areas of Brent Geese in Essex. The tidal distribution and productivity of the three species of Zostera is discussed, and results of surveys at Foulness and Osea Island are given. Z. noltii is the commonest species, and Z. marina is absent. Brent do not fully utilise all available supplies of Zostera. The behaviour of Brent in Essex is contrasted with areas where Z. marina is abundant. Enteromorpha is the commonest algal food. Important supplies are found at Dengie, Ray Sands and Goldhanger. Results of surveys at Goldhanger are given. More Brent eat Enteromorpha later in the winter; and in some areas Brent move between Enteromorpha and Zostera beds with the tide. Higher plants and animal foods are sometimes taken, and the ingestion of sand is discussed. Calculations of feeding rate based on measurement of grazing at Foulness suggest that food supplies in the main wintering haunts are more than adequate for the numbers of Brent recorded up to 1959-60. A reserve of food exists in other areas, and in theory could support considerably more; in practice, competition and the need for space to move about in would limit numbers. It is suggested that the highest winter average which would be comfortably maintained would be about 6000.